(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Oral tongue is one of the common site for carcinoma. 22% to 39% of oral cancer develops at this site. The high incidence of cervical lymph node metastasis, occult cervical metastasis, Provide a logical basis for treatment of the neck. The aim of this is study was to find out the importance of selective neck dissection in primary T1, T2, N0 Neck Oral Tongue Carcinoma. Methods: This cross-sectional study was conducted in the Department of Otolaryngology- Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College Hospital and National Institute of ENT, Dhaka. Thirty cases of primary T1, T2, N0 Neck Oral Tongue Carcinoma with inclusion criteria was enrolled as a study sample. Patients were evaluated by a complete clinical head and neck examination as well as Imaging (MRI) of the primary tumor and neck. All the data were compiled and sorted properly and the numerical data were analyzed statistically. The results were expressed as percentage and mean ± SD. Chi-square (x2) test or Fisher’s Exact test was done for comparison of data presented in categorical value and p value <0.05 was considered as the level of significance. Among the patients 23(76.7%) were T1 lesion and remaining 7(23.33%) were T2 lesion. Extended Supraomohyoid Selective Neck Dissection (SOSD) (I-IV) was done in all patients. Following histopathological examination, 8(26.67%) patients of N0 neck became positive for nodal metastasis. Results: The study showed that most commonly (50%) involved group of occult metastasis was upper deep cervical lymph node in submandibular area (level-I). Occult nodal metastasis was significantly common 87.5% among male patients than females (p=0.039) and also common 87.5% among <50 years age group (p=0.023). Neck node positive was significantly more 62.5% in T2 lesion (p=0.002) of oral tongue carcinoma. Conclusion: In this study, we found that a number of patients had been histopathologicallly detected micro-metastases in regional neck nodes in clinically N0 patients.So, Extended Supraomohyoid Selective neck dissection (I-IV) was appropriate in T1,T2, N0 Neck Oral Tongue Carcinoma. Bangladesh J Otorhinolaryngol 2021; 27(2): 130-138